Monitoring Surface Deformation Before the M7.0 Kumamoto and M6.6 Chitose Earthquakes for Precursor - Zulhamidi Nur Fatin Irdina; Abdullah Mardina; Nurul Shazana Abdul Hamid; Yusof Khairul Adib (E3S Web of Conferences)
Earthquakes have resulted in significant damage; however, the extent of the ground observation coverage remains limited. Thus, a deeper understanding of seismic activity and its precursors holds promise in mitigating earthquake hazards. This study aims to monitor the surface deformation for earthquake precursor identification. Interferometric Synthetic Aperture Radar (InSAR) observations were used to identify surface deformation before and after seismic events. The analysis of Sentinel-1 images provided a time series of land subsidence and deformation, allowing for the analysis of deformation evolution. A significant phase difference was observed between the preand post-event interferograms for both the Kumamoto and Chitose earthquakes. The phase map shows the phase difference caused by the energy released prior to the earthquake; hence, it could be a possible precursor for earthquakes. Developing strategies and implementing early warning systems could be effective in reducing the impact of earthquakes and protecting vulnerable regions from their severe consequences.